Efectos del COVID-19 en la pobreza multidimensional del Ecuador durante el período 2019-2020 (Estudios) - Quilli Granda, Karen Andrea (2024)
With the spread of the COVID-19 pandemic, poverty and inequality increased all over the world, and developing countries such as Ecuador were most affected ones. Considering this issue, this work was performed with the objective of analyzing the effects of COVID-19 on multi-dimensional poverty in Ecuador. For this purpose, the multi-dimensional poverty index was calculated, determining the absolute contribution of every poverty indicator on the index. The results obtained proved that Ecuador did have an increase of 1.11 points in the multi-dimensional poverty index between 2019 and 2020, mainly caused by the increase in unemployment and the lack of adequate employment. As such, it was proposed to make greater efforts in articulating and integrating government and civilian institutions to ensure full coverage of social assistance, as well as strengthening the social protection levels that exist in Ecuador.